ANTITOXIC ANTIDIFTHERIAL ANTIBODIES IN BLOOD SERA OF HEALTHY ADULTS UNDER DIFFERENT VACCINATION SCHEMES - E. A. Shmeleva; T. N. Firsova; S. M. Popkova; E. B. Rakova; L. V. Serdyuk; M. W. Gubin (Acta Biomedica Scientifica)
In this work intensity of immunity to diphtheria on the basis of indicating antitoxic antidiphtherial antiboies level in the blood sera of healthy adults aged 20 to 51 and elder, living in England, Italy, Latvia, Lithuania, Russia and Finland is analyzed. Diphtheria disease incidence shift through the epidemic in 1993—1996 in Russia to the elder age groups had resulted in inclusion of obligatory adults revaccination each 10 years after the last revaccination of teenagers in 14 year in 1998. Chosen tactics of vaccinal prevention of diphtheria didn't find reflection in National prophylactic immunization calendars of other countries including European, except Finland. On the basis of the received analysis for optimization of diphtheria vaccinal prevention, authors offer: to transfer a revaccination of children from age of 18 months to age of 3—6 years (according to the scheme in Italy, England, Finland); to carry out vaccination of adults individually depending on antitoxic antibodies concentration in blood sera.